Leukocytoclastic vasculitis in children: clinical characteristics, subtypes, causes and direct immunofluorescence findings of 56 biopsy‐confirmed cases. (19th September 2016) - Johnson, E.F.; Wetter, D.A.; Lehman, J.S.; Hand, J.L.; Davis, D.M.R.; Tollefson, M.M.
Abstract: Background: Leukocytoclastic vasculitis (LCV) in children is a complex group of conditions. Objectives: This study presents the demographics, clinical features, direct immunofluorescence (DIF) results and suspected aetiologies of 56 biopsy‐confirmed cases of leukocytoclastic vasculitis in children. Methods: Retrospective review of 56 children seen at Mayo Clinic in Rochester, Minnesota, from 1993 to 2013 with clinical features and cutaneous biopsy consistent with LCV. Results: Twenty‐seven (48%) cases were found to be due to IgA vasculitis (Henoch‐Schonlein purpura). The remaining cases were found to be due to cutaneous small‐vessel vasculitis ( n = 19, 34%), urticarial vasculitis ( n = 5, 9%), ANCA‐associated vasculitis ( n = 4, 7%) and acute haemorrhagic oedema of infancy ( n = 1, 2%). IgA vasculitis was found to be associated with abdominal pain ( P = 0.008), whereas the non‐IgA vasculitis group was associated with headache ( P = 0.052). Children with IgA vasculitis had palpable purpura ( P = <0.001), petechia ( P = 0.057), vesicles ( P = 0.009) and involvement of the buttock ( P = 0.004) more frequently than the non‐IgA vasculitis group. On DIF, perivascular IgA was positive in IgA vasculitis compared to non‐IgA vasculitis cases ( P = <0.001), the other conjugates were similar between the two groups. Conclusion: The most common subtype of biopsy‐confirmed LCV in children is IgA vasculitis. Clinical features, exam characteristics and DIF results can be helpful in determining the subtype of cutaneous vasculitis in children.